2020
DOI: 10.1155/2020/9526406
|View full text |Cite
|
Sign up to set email alerts
|

Successful Management of a Huge Pulmonary Hydatid Cyst with Lung-Preserving Surgery

Abstract: The lung is the second most commonly involved organ in humans by hydatid disease. Management of large pulmonary hydatid cysts is a great challenge for thoracic surgeons. Lung resections should be considered the last choice for huge pulmonary hydatid cysts when the lung expansion is not optimal after cyst removal. Here, we present a case of huge lung hydatid cyst involving the entire right lower lobe which was successfully managed by lung-preserving surgery in which the postoperative course showed gradual resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Hydatid cysts are more often located in the right lung and the lower lobes (13,16,17). The lower parts of the lungs are better vascularised than the upper ones allowing a good nutrition of the parasite ending in an easier growth (18).In our study, 67% cysts were found in the right lung and 53% in the basal lobes. In giant PCH, 66% were right and 62.5% in basal lobes.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Hydatid cysts are more often located in the right lung and the lower lobes (13,16,17). The lower parts of the lungs are better vascularised than the upper ones allowing a good nutrition of the parasite ending in an easier growth (18).In our study, 67% cysts were found in the right lung and 53% in the basal lobes. In giant PCH, 66% were right and 62.5% in basal lobes.…”
Section: Discussionsupporting
confidence: 45%
“…Medical treatment is indicated as a single treatment when surgery is contraindicated in case of inoperable patients due to cardiac and/or pulmonary performance status or in association with surgery when the cyst is ruptured in the pleural cavity (8,21) or in disseminated hydatid cysts to prevent postoperative recurrences (18). Medical treatment aims to reduce the number of cysts and to kill the parasite thus controlling hydatid dissemination and recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Parenchymapreserving procedures should be preferred in favorable cases, believing that underlying lung parenchyma beneath the cyst is healthy and might expand postoperatively. 16,17 Though there may not be a fair expansion of the remaining lobe at the time of surgery if there is no air leak then gradual expansion is expected later on. 17…”
Section: Ce Is a Zoonotic Parasitic Disease Caused Bymentioning
confidence: 99%
“…Human CE is treated by a variety of pharmacological and surgical methods ranging from chemotherapeutic treatment with albendazole and minimally invasive surgical treatments like PAIR (percutaneous Puncture, Aspiration, Injection, and Reaspiration) in asymptomatic patients [15,16]. There are various surgical procedures for pulmonary hydatid disease like enucleation, pericystectomy, cystostomy with capitonnage, cystostomy with the closure of the bronchial openings, and capitonnage, cystotomy with the closure of bronchial openings alone, open aspiration by Figuera technique, segmental resection, and lobectomy [17,18]. Currently, the most accepted surgical procedure for lung pulmonary is cystostomy methods that including intact cyst enucleation or removal after needle aspiration by maintaining the lung parenchyma as much as possible [14,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%